Terapi Diuretik: Furosemid dan Tiazid - Josephine Audi; Inda Meirani Herawita Br Sinaga (Jurnal Kedokteran Methodist, 2025)
Background: Diuretics are a primary pharmacological class used toregulate kidney function in the excretion of water and electrolytes, leadingto increased urine production and volume. The mechanism involves thesuppression of receptors responsible for the reabsorption of sodium(Na+)—the primary extracellular cation—within the renal tubules. Thisinhibition increases tubular osmolality, thereby suppressing waterreabsorption.Mechanism of Action: This study explores two major classes: Loopdiuretics and Thiazides. Loop diuretics exert their effect by inhibiting theNa+−K+−2Cl− (NKCC2) cotransporter on the apical membrane of thethick ascending limb of the loop of Henle. In contrast, Thiazides inhibitsodium-chloride (Na/Cl) channels in the distal convoluted tubules of thenephron.Synergistic Effect: Clinical evidence suggests that the addition ofThiazides can potentiate the efficacy of Loop diuretics. This synergyoccurs by inhibiting sodium reabsorption in the distal tubule and blockingthe compensatory responses—such as distal nephron hypertrophy—thattypically arise from long-term exposure to Loop diuretics.Conclusion: Understanding the distinct and combined mechanisms ofFurosemide and Thiazides is essential for optimizing fluid managementand overcoming diuretic resistance in clinical practice.Keywords: Diuretics, Furosemide, Thiazide, Renal Tubules, ElectrolyteExcretion.